Cyberbullying Patterns Psychological Impacts and Coping Strategies on Social Media among Adolescents - Andi Siti Aulia Akbar; Muh Fuad; Saif Mohammed (PT. Global Research Collaboration, 2025)
Background/Context: The rapid expansion of social media has transformed patterns of interaction among adolescents, creating opportunities for communication but also posing serious challenges such as cyberbullying. This phenomenon has become a significant concern due to its potential to harm victims’ self-confidence, social relationships, academic performance, and mental health.Objective/Purpose: This study aims to analyze patterns, impacts, preventive efforts, and personal attitudes toward cyberbullying on social media, as perceived by adolescents.Method: A quantitative descriptive approach with a cross-sectional design was employed. Data were collected from 71 respondents through a Likert-scale questionnaire covering four aspects: cyberbullying patterns, impacts, preventive measures, and personal attitudes.Results: The findings indicate that respondents strongly acknowledged the presence of cyberbullying patterns on social media, recognized its negative impacts on victims, emphasized the importance of preventive measures, and expressed firm personal attitudes against such behavior. The responses consistently reflected a shared recognition that cyberbullying is a serious issue in digital interactions.Conclusion: The study concludes that cyberbullying is a pervasive problem in adolescent social media use, requiring structured prevention strategies, legal reinforcement, digital literacy education, and collective participation. Collaborative efforts among individuals, communities, educators, and technology platforms are crucial to create safer and healthier online environments for young people.